Seed cone anatomy of cheirolepidiaceae (coniferales): Reinterpreting pararaucaria patagonica wieland - Escapa, Ignacio Hernán (2012)
• Premise of the study: Seed cone morphology and anatomy reflect some of the most important changes in the phylogeny and evolutionary biology of conifers. Reexamination of the enigmatic Jurassic seed cone Pararaucaria patagonica reveals previously unknown systematically informative characters that demonstrate affinities with the Cheirolepidiaceae. This paper documents, for the first time, internal anatomy for seed cones of this important extinct Mesozoic conifer family, which may represent the ghost lineage leading to modern Pinaceae. • Methods: Morphology and anatomy of cones from the Jurassic La Matilde Formation in Patagonia are described from a combination of polished wafers and thin section preparations. New photographic techniques are employed to reveal histological details of thin sections in which organic cell wall remains are not preserved. Specific terminology for conifer seed cones is proposed to help clarify hypotheses of homology for the various structures of the cones. • Key results: Specimens are demonstrated to have trilobed ovuliferous scale tips along with a seed enclosing pocket of ovuliferous scale tissue. Originally thought to represent a seed wing in P. patagonica, this pocket-forming tissue is comparable to the flap of tissue covering seeds of compressed cheirolepidiaceous cones and is probably the most diagnostic character for seed cones of the family. • Conclusions: Pararaucaria patagonica is assigned to Cheirolepidiaceae, documenting anatomical features for seed cones of the family and providing evidence for the antiquity of pinoid conifers leading to the origin of Pinaceae. A list of key morphological and anatomical characters for seed cones of Cheirolepidiaceae is developed to facilitate assignment of a much broader range of fossil remains to the family. This confirms the presence of Cheirolepidiaceae in the Jurassic of the Southern Hemisphere, which was previously suspected from palynological records.